Cardiac magnetic resonance imaging in patients with left bundle branch block: Patterns of dyssynchrony and implications for late gadolinium enhancement imaging - Petersen, Antonia; Nagel, Sebastian Niko; Hamm, Bernd; Elgeti, Thomas; Schaafs, Lars-Arne (Frontiers in Cardiovascular Medicine, 2022)
Background Left bundle branch block (LBBB) is a ventricular conduction delay with high prevalence. Aim of our study is to identify possible recurring patterns of artefacts in late gadolinium enhancement (LGE) imaging in patients with LBBB who undergo cardiac magnetic resonance imaging (MRI) and to define parameters of mechanical dyssynchrony associated with artefacts in LGE images. Materials and methods Fifty-five patients with LBBB and 62 controls were retrospectively included. Inversion time (TI) scout and LGE images were reviewed for artefacts. Dyssynchrony was identified using cardiac MRI by determining left ventricular systolic dyssynchrony indices (global, septal segments, and free wall segments) derived from strain analysis and features of mechanical dyssynchrony (apical rocking and septal flash). Results Thirty-seven patients (67%) with LBBB exhibited inhomogeneous myocardial nulling in TI scout images. Among them 25 (68%) patients also showed recurring artefact patterns in the septum or free wall on LGE images and artefacts also persisted in 18 (72%) of those cases when utilising phase sensitive inversion recovery. Only the systolic dyssynchrony index of septal segments allowed differentiation of patient subgroups (artefact/no artefact) and healthy controls (given as median, median ± interquartile range); LBBB with artefact: 10.44% (0.44–20.44%); LBBB without artefact: 6.82% (-2.18–15.83%); controls: 4.38% (1.38–7.38%); p < 0.05 with an area under the curve of 0.863 (81% sensitivity, 89% specificity). Septal flash and apical rocking were more frequent in the LBBB with artefact group than in the LBBB without artefact group (70 and 62% versus 33 and 17%; p < 0.05). Conclusion Patients with LBBB show recurring artefact patterns in LGE imaging. Use of strain analysis and evaluation of mechanical dyssynchrony may predict the occurrence of such artefacts already during the examination and counteract misinterpretation.